CIVIL LAW ASPECTS OF PROBLEMATIC DELIVERIES BY PT. POS INDONESIA CENTRAL JAKARTA BRANCH: A REVIEW OF LIABILITY AND DISPUTE RESOLUTION MECHANISMS - Kusmaputri, Reta Indah; Sakti, Muthia (Awang Long Law Review, 2025)
This study aims to examine the legal responsibilities of PT. Pos Indonesia Central Jakarta Branch in protecting consumers, with a specific focus on cases of lost, damaged, and delayed deliveries. The research adopts a normative legal methodology to analyze customer complaints and return data from 2023, as well as to review relevant legal frameworks under the Consumer Protection Law and the Postal Services Law. Special attention is given to the case of YouTuber Artodipro, whose import of non-nicotine cigarettes in excess of legal limits resulted in customs seizure, highlighting the intersection of postal services and import regulations. The scope of this study encompasses the legal obligations of PT. Pos Indonesia Central Jakarta in handling consumer complaints, the effectiveness of existing complaint resolution mechanisms, and the regulatory environment governing import restrictions for non-nicotine products. The findings reveal that the top five customer complaints relate to shipment information issues, misdelivery, pre-collecting, pickup requests, and item returns. The study concludes that PT. Pos Indonesia Central Jakarta is legally liable for ensuring compliance with delivery agreements and for providing compensation in cases of delay, loss, or damage. However, current complaint resolution processes are underutilized, and there is a lack of regulatory clarity and consumer awareness regarding import restrictions. In conclusion, PT. Pos Indonesia Central Jakarta is recommended to enhance its tracking systems, increase transparency in complaint handling, and streamline return processes. The study also suggests updating importation regulations for non-nicotine products and improving consumer education on customs procedures to strengthen consumer protection and regulatory compliance.